Dynamics of Hotel Financial Performance Based on Operational and Profitability Indicators: A Case Study of Hotel Mercure Bandung Nexa Supratman - Lesfandra Lesfandra; Dony Oktariswan (SEAN Institute, 2026)
This study aims to analyze the financial performance dynamics of the Mercure Bandung Nexa Supratman Hotel during the 2022–2025 period based on operational and profitability indicators. The study uses a quantitative descriptive approach with a case study method. Secondary data were obtained from the hotel's internal management reports on Occupancy Rate (OR), Average Daily Rate (ADR), Revenue per Available Room (RevPAR), Gross Operating Profit (GOP), as well as Budget and Actual data. The analysis was conducted using Trend Analysis, Growth Analysis, and Budget versus Actual Analysis. The results show that Occupancy Rate, ADR, RevPAR, Total Revenue, and GOP fluctuated during the study period. Hotel performance increased until 2024, but declined in 2025 as indicated by declining occupancy rates, revenue, and profitability. Budget versus Actual analysis shows a favourable variance in 2022–2024 and an unfavourable variance in 2025. These findings indicate that increased revenue is not always followed by increased profitability because it is influenced by operational cost control. The novelty of research on the integration of operational indicators, profitability, and budget achievement in a single evaluation framework for the dynamics of hotel financial performance as a basis for strategic decision making.